Functions of TNF-α1 and TNF-α2 in large yellow croaker (Larimichthys crocea) in monocyte/macrophage activation. (April 2020) - Huang, Mingyue; Mu, Pengfei; Li, Xiaofeng; Ren, Qiulei; Zhang, Xiang-Yang; Mu, Yinnan; Chen, Xinhua
Abstract: Tumor necrosis factor-α (TNF-α) plays crucial roles in cell development, proliferation, apoptosis, inflammation, and immunity. TNF-α genes have been identified in various fish species, however, their biological functions remain to be further clarified. In this study, we identified a novel TNF-α homologue ( Lc TNF-α2) from large yellow croaker ( Larimichthys crocea ), which shares a low amino acid sequence identity to the previously reported large yellow croaker TNF-α ( Lc TNF-α1). The open reading frame of Lc TNF-α2 is 714 nucleotides long, encoding a peptide of 237 amino acids (aa). The deduced Lc TNF-α2 protein contains a 23-aa transmembrane region, a TACE restriction site at residues T 71 /L 72, a TNF family signature (I 108 – F 135 ), and two conserved cysteine residues (C 39 and C 179 ), as found in other known TNF-α sequences. Both Lc TNF-α1 and Lc TNF-α2 genes were constitutively expressed in all examined tissues and significantly up-regulated in the spleen and head kidney by Vibrio alginolyticus . Their transcripts were also detected in primary head kidney monocytes/macrophages (MO/Mϕs), lymphocytes (PKLs), granulocytes (PKGs), and large yellow croaker head kidney (LYCK) cell line and significantly increased in these cell types by inactivated Vibrio alginolyticus . Recombinant Lc TNF-α1 and Lc TNF-α2 proteins (rLcTNF-α1 and rLcTNF-α2) produced in Pichia pastoris not only significantly increased the production of reactive oxygen species (ROS), but also promoted the expression of proinflammatory cytokines (IL-1β, IL-6, IL-8, and TNF-α1) in MO/Mϕs from large yellow croaker. Even more, after stimulation with rLcTNF-α1 and rLcTNF-α2, the production of nitrogen oxide (NO) and the expression of inducible NO synthase (iNOS) gene were significantly up-regulated. However, only rLcTNF-α1 remarkedly enhanced the phagocytosis of MO/Mϕs and increased the expression of TNF-α2 in MO/Mϕs. These results therefore indicated that Lc TNF-α1 and Lc TNF-α2 both play roles in promoting activation of head kidney MO/Mϕs. Highlights: A novel TNF-α homologue ( Lc TNF-α2) from large yellow croaker was identified. Recombinant Lc TNF-α1 (rLcTNF-α1) and rL c TNF-α2 increase ROS production and proinflammatory cytokine expression in MO/Mφs. NO production and iNOS expression can be significantly up-regulated by rL c TNF-α1 and rL c TNF-α2. Only rLcTNF-α1 can markedly enhance phagocytosis of MO/Mφs and increase expression of TNF-α2.